The Legal Protection of Criminal Action on Child Addiction - Saharuddin Saharuddin; Suardi Rais; Rasty Amalia Farouk (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2022)
The aims of this research is the practice of abdicating responsibility and illegally claiming offspring on Child neglect. This is due to such as economic and social factors and mental illness. The law explicitly designs forms of child protection as stated in Article 5 of Act No. 23 of 2004